APPROACH TO DESIGN OF FACTORIAL SOLUTIONS OF WOMEN'S CLOTHES - Михайлюк, О. Ю.; Остапенко, Н. В.; Луцкер, Т. В. (Art and Design, 2019)
The purpose of the article is to determine the preconditions of design of factured solutions of artistic-expressive products. In the course of research, a complex of general scientific approaches was used: visual-analytical, system-informational and the method of classifications. The artistic and aesthetic approach to the design of products with facture effects is offered. The constituent elements of the mentioned approach are determined and characterized, their specificity is disclosed. The artistic and aesthetic features of women's clothing with factured effects are researched. The prerequisites for the formation of the information base of factures varieties for the purpose of artistically expressive women's clothing models designing are outlined. Scientific novelty. On the basis of theoretical researches, an artistic and aesthetic approach to the design of products with factured effects has been developed and its components have been substantiated. Dependence of the characteristics of the materials varieties from products with facture effects was revealed. The criteria for assessing the artistic and aesthetic characteristics of women's clothing with factured effects are formulated. The offered criteria of estimation of products of women's clothes are characterized. The possibility of forecasting the perception of a harmonic image on the basis of its color-factorial solution is proved. Practical significance. The information base of the types of factures is formed and the most common ones are identified with the aim of improving design and expanding the range of new product models. Recommendations on the application of various facture effects in women's clothing are formulated.